Maternal and Environmental Determinants of Linear and Cranial Growth: A 6-Year Longitudinal Study in West Sumatra - Ulya Uti Fasrini; Nur Afrainin Syah; Joserizal Serudji; Nur Indrawaty Lipoeto (Media Publikasi Cendekia Indonesia, 2026)
This study aimed to identify the integrated maternal, environmental, and biological predictors of child linear growth (Height-for-Age Z-score; HAZ) and cranial growth (Head Circumference; HC) at age six in a longitudinal Indonesian cohort. A prospective cohort study followed 120 mother-child pairs in West Sumatra from the first trimester of pregnancy (2017) through age six (2023). Data were collected on maternal nutrient intake (SQ-FFQ), Vitamin D status (serum 25(OH)D), physical activity, and environmental conditions. Integrated multiple linear regression models were constructed to determine independent predictors, adjusted for maternal education and prepregnancy BMI. In the final integrated models, child HAZ at age six was significantly predicted by maternal first-trimester energy intake (β = 0.0006, p = 0.006), maternal height (p = 0.012), and child energy intake (p = 0.005). Cranial growth (HC) was primarily predicted by birth weight (β=0.0011, p=0.004) and maternal physical activity index (p=0.031). Maternal Vitamin D sufficiency (≥30 ng/mL) in the first trimester showed higher mean HAZ and HC compared to deficient levels (<20 ng/mL), although these differences were not statistically significant. The findings indicate that early pregnancy may be an important period for establishing growth trajectories, shaped by maternal nutritional status and environmental conditions. These observations support the potential value of strengthening pre-conception and early pregnancy care, including nutritional optimization and access to safe water; however, further studies are required to confirm these patterns and inform targeted interventions in West Sumatra.